ANALISIS DAN PERANCANGAN SISTEM INFORMASI KOPERASI SIMPAN PINJAM BERBASIS WEB PADA MTs NEGERI TALANG BAKUNG KOTA JAMBI - Wati, Herly Kusuma; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2017)
The management of a good information system produces ease in accessing information data foran organization. For ease of accessing the information required integration between informationsystems, with the existence of various computer information system it will facilitate andaccelerate the process of management in the field of business one form of business that requiresthe management of computer based information system is a cooperative effort. Data is still donemanually.The objectives in the study are to analyze and study the problems of savings and loan basedcooperative information system on MTs Negeri Talang Bakung. System design in this researchusing UML tool (United Modelling Language) that is Use Case diagram, activity diagram andclass diagram. While in making prototype system using adobe dreamweaver and to designdatabase using MySQL. In this research produce prototype information system of web basedsavings and loan cooperative at MTs Negeri Talang Bakung which can manage.